The Effectiveness of Experiential Methods in Training and Education: The Case of Role Playing - Kidron, Aryeh G. (Academy of Management Review, 1977)
In this article the author examines the effectiveness of role playing exercises in research, social work, counseling and other disciplines. The author notes that role playing exercises are defined as a dynamic process that involves participants assuming specified roles and acting out significant events. He discusses some pervious studies on role playing that found that participants expressed greater confidence in their opinions, that attitudes could be changed and that creativity could be bolstered by role playing.